Baby Shark and William's big adventure (Ashland, OH Bendon/PinkFong)
"Join Baby Shark and his friend William as they embark on big adventures under the sea. From exploring hidden treasures to meeting new ocean friends, each page brings a new discovery that keeps young readers engaged."
Ages 5-7. K to Grade 1.
Keywords: sharks -- picture books